Regulation of adult-born and mature neurons in stress response and antidepressant action in the dentate gyrus of the hippocampus - Eri Segi-Nishida; Kanzo Suzuki (Neuroscience Research)
The dentate gyrus (DG) of the hippocampus has been implicated in the regulation of stress responses, and in the pathophysiology and treatment of depression. This review discusses the cellular changes caused by chronic stress and the cellular role of the DG in stress-induced behavioral changes and its antidepressant-like effects. Regarding adult-born neurogenic processes in the DG, chronic stress, such as repeated social defeat, suppresses cell proliferation during and immediately after stress; however, this effect is transient. The subsequent differentiation and survival processes are differentially regulated depending on the timing and sensitivity of stress. The activation of young adult-born neurons during stress contributes to stress resilience, while the transient increase in the survival of adult-born neurons after the cessation of stress seems to promote stress susceptibility. In mature granule neurons, the predominant cells in the DG, synaptic plasticity is suppressed by chronic stress. However, a group of mature granule neurons is activated by chronic stress. Chronic antidepressant treatment can transform mature granule neurons to a phenotype resembling that of immature neurons, characterized as “dematuration”. Adult-born neurons suppress the activation of mature granule neurons during stress, indicating that local neural interactions within the DG are important for the stress response. Elucidating the stress-associated context- and timing-dependent cellular changes and functions in the DG will provide insights into stress-related psychiatric diseases.